Retrograde Bone Morphogenetic Protein Signaling Shapes a Key Circadian Pacemaker Circuit - Gorostiza, Ezequiel Axel (2013)
The neuropeptide pigment-dispersing factor (PDF) synchronizes molecular oscillations within circadian pacemakers in the Drosophila brain. It is expressed in the small ventral lateral neurons (sLNvs) and large ventral lateral neurons, the former being indispensable for maintaining behavioral rhythmicity under free-running conditions. How PDF circuits develop the specific connectivity traits that endow such global behavioral control remains unknown. Here, we show that mature sLNv circuits require PDF signaling during early development, acting through its cognate receptor PDFR at postsynaptic targets. Yet, axonal defects by PDF knockdown are presynaptic and become apparent only after metamorphosis, highlighting a delayed response to a signal released early on. Presynaptic expression of constitutively active bone morphogenetic protein (BMP) receptors prevents pdfr mutants misrouting phenotype, while sLNv-restricted downregulation of BMP signaling components phenocopied pdf(01). Thus, we have uncovered a novel mechanism that provides an early "tagging" of synaptic targets that will guide circuit refinement later in development.